Agglutination polypeptide and application thereof

Through the preparation process of specific polypeptide combinations and high-substituted sodium hydroxymethylcellulose, a aggregation polypeptide was constructed, which solved the shortcomings of the drug delivery system in terms of structural stability, drug load efficiency and biocompatibility, and achieved the Efficient and safe drug delivery effects.

CN119454982APending Publication Date: 2025-02-18ZHEJIANG YINKAI BIOMEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411746548.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18

Smart Images

  • Figure CN119454982A_ABST
    Figure CN119454982A_ABST
Patent Text Reader

Abstract

The invention discloses agglutination polypeptide and application thereof, and belongs to the technical field of agglutination polypeptide, and the agglutination polypeptide comprises the following components in parts by weight: 20-30 parts of polylysine polypeptide, 15-25 parts of polyglutamic acid polypeptide, 10-18 parts of arginine oligopeptide, 8-15 parts of high-substitution-degree carboxymethyl cellulose sodium, 5-12 parts of sodium alginate and 3-8 parts of gallic acid. According to the invention, an aggregate capturing drug is formed by utilizing electrostatic, hydrophobic and hydrogen-bond interaction of arginine oligopeptide and aspartic acid oligopeptide, and a network structure is constructed on the surface of the aggregate by virtue of multiple crosslinking of high-substitution-degree carboxymethyl cellulose sodium, sodium alginate and gallic acid; and the hydrogel has strong drug loading transport capacity, biomolecule activity retention, cell penetration capacity and biocompatibility. The high-substituted carboxymethyl cellulose sodium can reinforce the structure of the aggregate, enhance the stability of the aggregate in in-vivo and in-vitro environments, assist drug adhesion through physical adsorption or weak interaction, improve the loading efficiency, avoid premature leakage or loss of drugs, and powerfully enhance the drug loading capacity of the drug delivery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of agglutination polypeptides, and in particular relates to an agglutination polypeptide and an application thereof. Background Art

[0002] In the field of modern drug delivery technology, traditional drug delivery systems have always faced many difficulties. Their circulatory stability is poor, which often leads to premature or excessive release of drugs, making it difficult to accurately deliver drugs to the target site, thus failing to optimize the therapeutic effect. Although microenvironment-responsive drug delivery systems have been tried in the treatment of various diseases, the synthesis of such nanoparticles is extremely complex. Most of them rely on passive adsorption of drugs to achieve drug loading purposes, and this drug loading method results in a low loading efficiency. Moreover, the raw materials used to synthesize nanoparticles usually only serve as simple carriers. After large-scale accumulation in the body, they are likely to cause adverse reactions and pose a potential threat to human health.

[0003] As an emerging form of nanoparticles, coacervates have received extensive attention in recent years. Coacervates are dense liquid coacervates formed by liquid-liquid phase separation in a high-concentration biomolecule environment through multiple interactions such as electrostatic interactions, hydrophobic interactions, π stacking, and hydrogen bonding. Its particle size is in the nanometer or micrometer range, and its appearance is similar to that of an emulsion, and it does not require the assistance of stabilizing molecules such as surfactants. Coacervates can concentrate and encapsulate drugs inside and release drugs by regulating their own properties. However, coacervates still have some limitations in practical applications, such as the need to further improve their structural stability in complex in vitro and in vivo environments, the need to further improve drug loading efficiency, and the need for further optimization in terms of biocompatibility to better meet the requirements of drug delivery systems.

[0004] Sodium carboxymethyl cellulose, also known as sodium carboxymethyl cellulose, carboxymethyl cellulose, CMC, etc., is the most widely used and largest amount of cellulose in the world. It is referred to as CMC-Na. It is a cellulose derivative with a glucose polymerization degree of 100-2000, a relative molecular mass of 242.16, and is a white fibrous or granular powder. It is odorless, tasteless, hygroscopic, and insoluble in organic solvents. Substituted CMC usually refers to a high degree of substitution, which can generally reach more than 0.85, and the purity of CMC is high. It is suitable for medical, food and other technical fields. For example, the purity of CMC used as a thickener in the food industry must reach 99.5% or more, and it can be used as a drug carrier in the pharmaceutical industry. However, how to use sodium carboxymethyl cellulose to effectively solve the technical problems faced by the coacervate in the drug delivery process, such as insufficient structural stability, low drug loading efficiency, and unsatisfactory biocompatibility, has become the focus and difficulty of current research in the field of drug delivery technology. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention realizes the construction of an agglutination polypeptide with high stability, efficient drug loading and good biocompatibility and its effective application in a drug delivery system through a specific polypeptide combination and a unique preparation process of high-degree-of-substitution sodium hydroxymethyl cellulose.

[0006] In order to achieve the above-mentioned purpose, the following technical scheme is adopted: on the one hand, the present invention provides a coagulation polypeptide, comprising the following components in parts by weight: 20-30 parts of polylysine polypeptide, 15-25 parts of polyglutamic acid polypeptide, 10-18 parts of arginine oligopeptide, 8-15 parts of highly substituted sodium hydroxymethyl cellulose, 5-12 parts of sodium alginate and 3-8 parts of gallic acid.

[0007] Furthermore, the highly substituted sodium hydroxymethyl cellulose is prepared by the following steps:

[0008] S1: adding potassium hydroxide to water to prepare a potassium hydroxide solution with a mass fraction of 12-15%, adding sodium sulfite to the potassium hydroxide solution and stirring evenly, then adding copper sulfate, adjusting the temperature to 65-70° C., keeping the temperature and stirring for 40 minutes, to obtain a mixed solution;

[0009] S2: adding pine pollen to the mixed solution obtained in step S1, stirring at a speed of 1200 r / min for 4-5 hours, standing for 1.5 hours, performing reduced pressure distillation and drying to constant weight to obtain an intermediate;

[0010] S3: Mix the intermediate obtained in step S2 with the mixed solution, adjust the temperature to 45° C., keep warm and stir for 1.5 hours, then add etherifying agent potassium bromoacetate to carry out etherification treatment for 2.5 hours, neutralize with citric acid to neutrality after the reaction, repeatedly wash with 75% isopropanol solution, and finally perform reduced pressure distillation and dry to constant weight to obtain the highly substituted sodium hydroxymethyl cellulose.

[0011] Furthermore, the mesh size of the pine pollen is 80-120 meshes.

[0012] Furthermore, in step S1, the mass fraction of sodium sulfite is 3.5-4.5%, and the mass fraction of copper sulfate is 0.2-0.25%.

[0013] Furthermore, in step S2, the mass ratio of pine wood powder to new mixed liquid is 1:8-10.

[0014] Furthermore, in step S3, the mass ratio of the intermediate to the mixed liquid is 1:13-20.

[0015] Furthermore, in step S3, the mass ratio of potassium bromoacetate to the intermediate is 2.5-5:1.

[0016] Furthermore, the average molecular weight of the poly-lysine polypeptide is 700,000-1.5 million.

[0017] Furthermore, the average molecular weight of the polyglutamic acid polypeptide is 150,000-3,000,000.

[0018] Furthermore, the number of oligopeptides in the arginine oligopeptide is greater than 5.

[0019] On the other hand, the present invention also provides a use of an agglutination polypeptide in a drug delivery system, wherein the pH targeted controlled release range of the agglutination polypeptide is 7.0-8.0.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention utilizes the electrostatic interaction, hydrophobic interaction and hydrogen bonding between positively charged arginine oligopeptide and negatively charged aspartic acid oligopeptide to form a coacervate in the solution, which can efficiently capture drugs and provide a strong guarantee for drug loading. With the help of multiple cross-linking interactions formed by highly substituted sodium hydroxymethyl cellulose, sodium alginate and gallic acid, a layer of network structure is wrapped on the surface of the coacervate, which greatly improves the stability, microenvironment responsiveness and operability of the coacervate, thereby constructing an efficient drug delivery system, which has microenvironment responsiveness, strong drug loading and transportation capacity, can maintain the activity of biological molecules, has good cell penetration ability, and also has good biocompatibility;

[0022] (2) The highly substituted sodium hydroxymethyl cellulose prepared by the present invention can strengthen the structure of the coacervate, making it less likely to disintegrate or undergo structural damage in complex in vitro and in vivo environments, thereby effectively improving the stability of the coacervate, ensuring that it always maintains its intact structure during the drug delivery process and better exerts its drug delivery function. At the same time, it can help the drug to better adhere to the coacervate through physical adsorption or form specific weak interactions with drug molecules, significantly improving the drug loading efficiency, ensuring that the drug can be stably wrapped by the coacervate, preventing the drug from leaking prematurely or accidentally dissipating during the delivery process, thereby greatly enhancing the drug loading capacity of the drug delivery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The cytotoxicity test results of the agglutination polypeptides prepared in various embodiments and comparative examples of the present invention;

[0024] Figure 2 The drug encapsulation efficiency test results of the agglutinated polypeptides prepared in various embodiments and comparative examples of the present invention;

[0025] Figure 3The drug release rate test results of the agglutinated polypeptides prepared in various embodiments and comparative examples of the present invention are shown.

[0026] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0030] Example 1

[0031] Agglutination polypeptide and its application

[0032] The agglutination polypeptide comprises the following components in parts by weight: 20 parts of polylysine polypeptide, 15 parts of polyglutamic acid polypeptide, 10 parts of arginine oligopeptide, 8 parts of highly substituted sodium hydroxymethylcellulose, 5 parts of sodium alginate and 3 parts of gallic acid.

[0033] The highly substituted sodium hydroxymethyl cellulose is prepared by the following steps:

[0034] S1: adding potassium hydroxide to water to prepare a potassium hydroxide solution with a mass fraction of 12%, adding sodium sulfite to the potassium hydroxide solution and stirring evenly, then adding copper sulfate, adjusting the temperature to 65° C., and stirring for 40 minutes to obtain a mixed solution;

[0035] S2: adding pine pollen to the mixed solution obtained in step S1, stirring at a speed of 1200 r / min for 4-5 hours, standing for 1.5 hours, performing reduced pressure distillation and drying to constant weight to obtain an intermediate;

[0036] S3: Mix the intermediate obtained in step S2 with the mixed solution, adjust the temperature to 45° C., keep warm and stir for 1.5 hours, then add etherifying agent potassium bromoacetate to carry out etherification treatment for 2.5 hours, neutralize with citric acid to neutrality after the reaction, repeatedly wash with 75% isopropanol solution, and finally perform reduced pressure distillation and dry to constant weight to obtain the highly substituted sodium hydroxymethyl cellulose.

[0037] The mesh number of the pine pollen is 80-120 meshes.

[0038] In step S1, the mass fraction of sodium sulfite is 3.5%, and the mass fraction of copper sulfate is 0.2%.

[0039] The mass ratio of the pine wood powder to the new mixed liquid in step S2 is 1:8.

[0040] The mass ratio of the intermediate to the mixed liquid in step S3 is 1:13.

[0041] In step S3, the mass ratio of potassium bromoacetate to the intermediate is 2.5:1.

[0042] The average molecular weight of the poly-lysine polypeptide is 700,000.

[0043] The average molecular weight of the polyglutamic acid polypeptide is 150,000.

[0044] The number of oligopeptides on the arginine oligopeptide is greater than 5.

[0045] When the agglutination polypeptide is used in a drug delivery system, the pH targeted controlled release range of the agglutination polypeptide is 7.0-8.0.

[0046] Example 2

[0047] Agglutination polypeptide and its application

[0048] The agglutination polypeptide comprises the following components in parts by weight: 30 parts of polylysine polypeptide, 25 parts of polyglutamic acid polypeptide, 18 parts of arginine oligopeptide, 15 parts of highly substituted sodium hydroxymethylcellulose, 12 parts of sodium alginate and 8 parts of gallic acid.

[0049] The highly substituted sodium hydroxymethyl cellulose is prepared by the following steps:

[0050] S1: adding potassium hydroxide to water to prepare a potassium hydroxide solution with a mass fraction of 15%, adding sodium sulfite to the potassium hydroxide solution and stirring evenly, then adding copper sulfate, adjusting the temperature to 70° C., and stirring for 40 minutes to obtain a mixed solution;

[0051] S2: adding pine pollen to the mixed solution obtained in step S1, stirring at a speed of 1200 r / min for 4-5 hours, standing for 1.5 hours, performing reduced pressure distillation and drying to constant weight to obtain an intermediate;

[0052] S3: Mix the intermediate obtained in step S2 with the mixed solution, adjust the temperature to 45° C., keep warm and stir for 1.5 hours, then add etherifying agent potassium bromoacetate to carry out etherification treatment for 2.5 hours, neutralize with citric acid to neutrality after the reaction, repeatedly wash with 75% isopropanol solution, and finally perform reduced pressure distillation and dry to constant weight to obtain the highly substituted sodium hydroxymethyl cellulose.

[0053] The mesh number of the pine pollen is 80-120 meshes.

[0054] In step S1, the mass fraction of sodium sulfite is 4.5%, and the mass fraction of copper sulfate is 0.25%.

[0055] The mass ratio of the pine wood powder to the new mixed liquid in step S2 is 1:10.

[0056] The mass ratio of the intermediate to the mixed liquid in step S3 is 1:20.

[0057] In step S3, the mass ratio of potassium bromoacetate to the intermediate is 5:1.

[0058] The average molecular weight of the poly-lysine polypeptide is 1.5 million.

[0059] The average molecular weight of the polyglutamic acid polypeptide is 3 million.

[0060] The number of oligopeptides on the arginine oligopeptide is greater than 5.

[0061] When the agglutination polypeptide is used in a drug delivery system, the pH targeted controlled release range of the agglutination polypeptide is 7.0-8.0.

[0062] Example 3

[0063] Agglutination polypeptide and its application

[0064] The agglutination polypeptide comprises the following components in parts by weight: 25 parts of polylysine polypeptide, 20 parts of polyglutamic acid polypeptide, 15 parts of arginine oligopeptide, 10 parts of highly substituted sodium hydroxymethylcellulose, 8 parts of sodium alginate and 5 parts of gallic acid.

[0065] The highly substituted sodium hydroxymethyl cellulose is prepared by the following steps:

[0066] S1: adding potassium hydroxide to water to prepare a potassium hydroxide solution with a mass fraction of 13%, adding sodium sulfite to the potassium hydroxide solution and stirring evenly, then adding copper sulfate, adjusting the temperature to 68° C., and stirring for 40 minutes to obtain a mixed solution;

[0067] S2: adding pine pollen to the mixed solution obtained in step S1, stirring at a speed of 1200 r / min for 4-5 hours, standing for 1.5 hours, performing reduced pressure distillation and drying to constant weight to obtain an intermediate;

[0068] S3: Mix the intermediate obtained in step S2 with the mixed solution, adjust the temperature to 45° C., keep warm and stir for 1.5 hours, then add etherifying agent potassium bromoacetate to carry out etherification treatment for 2.5 hours, neutralize with citric acid to neutrality after the reaction, repeatedly wash with 75% isopropanol solution, and finally perform reduced pressure distillation and dry to constant weight to obtain the highly substituted sodium hydroxymethyl cellulose.

[0069] The mesh number of the pine pollen is 80-120 meshes.

[0070] In step S1, the mass fraction of sodium sulfite is 4%, and the mass fraction of copper sulfate is 0.21%.

[0071] The mass ratio of the pine wood powder to the new mixed liquid in step S2 is 1:9.

[0072] The mass ratio of the intermediate to the mixed liquid in step S3 is 1:15.

[0073] In step S3, the mass ratio of potassium bromoacetate to the intermediate is 3:1.

[0074] The average molecular weight of the poly-lysine polypeptide is 1 million.

[0075] The average molecular weight of the polyglutamic acid polypeptide is 1.5 million.

[0076] The number of oligopeptides on the arginine oligopeptide is greater than 5.

[0077] When the agglutination polypeptide is used in a drug delivery system, the pH targeted controlled release range of the agglutination polypeptide is 7.0-8.0.

[0078] Comparative Example 1

[0079] The difference between this comparative example and Example 3 is that commercially available sodium hydroxymethyl cellulose is used instead of sodium hydroxymethyl cellulose with a high degree of substitution, and the rest is the same as Example 3.

[0080] Comparative Example 2

[0081] The difference between this comparative example and Example 3 is that the components of the agglutinated polypeptide lack sodium alginate, and the rest are the same as Example 3.

[0082] Comparative Example 3

[0083] The difference between this comparative example and Example 3 is that the component of the agglutinating polypeptide lacks gallic acid, and the rest is the same as Example 3.

[0084] Results Analysis

[0085] Test Example 1

[0086] Cytotoxicity assay

[0087] Test results see Figure 1 , specifically including the following steps:

[0088] (1) Cell culture: Human hepatoma cell HepG2 were seeded in a 96-well plate at a density of 5,000 cells per well and cultured in a 37°C, 5% CO2 incubator for 24 hours to allow the cells to adhere to the plate and grow;

[0089] (2) Adding samples and culturing: discard the old culture medium, add agglutinating polypeptide solutions with concentrations of 0, 2, 3.9, 7.8, 15.6, 31.2, 62.5, 125, 250 and 500 μM, respectively, set up 3-6 replicate wells for each concentration, and set up a blank control group (only culture medium), and continue to culture in a 37°C, 5% CO2 incubator for 24-72 hours;

[0090] (3) Detection: After the incubation, remove the 96-well plate, add 20 μL of MTT solution (concentration of 5 mg / mL) to each well, incubate at 37°C in the dark for 4 h, then carefully remove the liquid in the wells, add 150 μL of DMSO to each well, shake for 10-15 min to fully dissolve the crystals, and measure the absorbance (OD value) at a wavelength of 570 nm using an enzyme reader;

[0091] (4) Calculate cell viability: Cell viability (%) = (OD value of experimental group - OD value of blank group) / (OD value of control group - OD value of blank group) × 100%.

[0092] from Figure 1It can be seen that the cytotoxicity of the agglutinating polypeptides in Examples 1-3 to human liver cancer cells HepG2 at different concentrations is low. In the low concentration range, the cell viability is basically maintained at a high level. Even at a higher concentration, a certain proportion of the cell viability is still retained, which shows that the agglutinating polypeptide of the present invention has good biocompatibility, which is due to the reasonable combination of the components in the agglutinating polypeptide, the interaction between the arginine oligopeptide and the polyglutamic acid polypeptide to form a coacervate, and the multiple cross-linked structure formed by the high-degree-of-substitution sodium hydroxymethylcellulose, sodium alginate and gallic acid, so that the coacervate will not cause excessive damage to the cells during the interaction with the cells. injury, can maintain the activity of biological molecules, and has good cell penetration ability, thereby reducing the adverse effects on normal tissue cells during drug delivery; after using commercially available sodium hydroxymethyl cellulose instead of high-substituted sodium hydroxymethyl cellulose in Comparative Example 1, the cell viability was lower than that in Example 3 at the same concentration, especially at higher concentrations, the decrease was more obvious, which shows that the high-substituted sodium hydroxymethyl cellulose prepared by the present invention helps to improve the biocompatibility of the agglutinated polypeptide as a whole, and its special preparation process and structure may enable it to better regulate the interaction between the agglomerate and the cells when synergizing with other components, thereby reducing the toxicity to the cells.

[0093] Test Example 2

[0094] Drug encapsulation efficiency test

[0095] Test results see Figure 2 , specifically including the following steps:

[0096] (1) Mixing drugs and agglutinating polypeptides: Accurately weigh 5 mg of doxorubicin and dissolve it in 5 mL of PBS buffer solution to prepare a doxorubicin solution with a concentration of 1 mg / mL;

[0097] Take 2 mL of 1 mg / mL doxorubicin solution and 3 mL of 50 mg / mL agglutination polypeptide solution (agglutination polypeptide solution preparation: weigh an appropriate amount of agglutination polypeptide and dissolve it in PBS to make its concentration 50 mg / mL) and mix them to make the drug and agglutination polypeptide fully contact, and incubate at 37°C for 3 hours to promote drug encapsulation;

[0098] (2) Separation of unencapsulated drugs: The mixed solution was transferred to a dialysis bag and dialyzed with 500 mL of PBS buffer solution under magnetic stirring. The dialysis external solution was replaced every 1.5 hours for 24 hours to remove unencapsulated drugs.

[0099] (3) Determination of drug content: Since doxorubicin has a characteristic absorption spectrum, a UV-visible spectrophotometer was used to measure the absorbance of the solution in the dialysis bag at the characteristic absorption wavelength of doxorubicin (480 nm);

[0100] (4) Pre-draw the standard absorbance-concentration curve of doxorubicin: prepare a series of doxorubicin standard solutions of different concentrations (such as 0.1 μg / mL, 0.2 μg / mL, 0.5 μg / mL, 1 μg / mL, 2 μg / mL, 5 μg / mL), measure their absorbance values ​​at 480 nm, and draw the standard curve. According to the absorbance value of the solution in the dialysis bag, calculate the concentration of the drug in the dialysis bag from the standard curve, that is, the concentration of the encapsulated drug (C1);

[0101] (5) Calculation of drug encapsulation efficiency: The total drug concentration initially added (C2) was 0.4 mg / mL;

[0102] Drug encapsulation efficiency (%) = (C1 / C2) × 100%.

[0103] Depend on Figure 2 It can be seen that the drug encapsulation rates of Examples 1-3 are all at a relatively high level. This is because the electrostatic interaction, hydrophobic interaction and hydrogen bonding between the positively charged arginine oligopeptide and the negatively charged polyglutamic acid polypeptide enable them to form aggregates in the solution, which can efficiently capture the drug and provide a strong guarantee for the loading of the drug. At the same time, the highly substituted sodium hydroxymethyl cellulose can help the drug to better adhere to the aggregates through physical adsorption or the formation of specific weak interactions with the drug molecules, significantly improving the loading efficiency of the drug, ensuring that the drug can be stably encapsulated by the aggregates, and preventing the drug from leaking prematurely or accidentally lost during the delivery process.

[0104] In Example 1, commercially available sodium hydroxymethyl cellulose is used, and its drug encapsulation efficiency is significantly lower than that of Example 3, indicating that the high-substituted sodium hydroxymethyl cellulose prepared by the present invention has unique advantages in improving the drug encapsulation efficiency. Its special structure and properties can better interact with drug molecules, enhance the adsorption and encapsulation ability of the coacervate for drugs, thereby improving the drug loading capacity of the drug delivery system.

[0105] Test Example 3

[0106] Drug release rate testing

[0107] Test results see Figure 3 , specifically including the following steps:

[0108] (1) Preparation of drug-loaded agglutination polypeptide sample: Prepare 2 μg / mL drug-loaded agglutination polypeptide sample according to the method in Experimental Example 2 and transfer it to a dialysis bag;

[0109] (2) Release experiment: The dialysis bag containing the drug-loaded aggregated polypeptide was placed in 100 mL of PBS release medium, and the drug release experiment was performed in a constant temperature shaking incubator at 37°C and an shaking speed of 100 rpm;

[0110] (3) Timed sampling: 1.5 mL of release medium was taken out at 0.5 h, 1 h, 2 h, 4 h, 8 h, 12 h, 24 h, 48 h, etc., and an equal amount of fresh release medium was added;

[0111] (4) Determination of drug content: According to the method for determining the content of doxorubicin in Experimental Example 2, the concentration of doxorubicin in the release medium at different time points (C3) was determined;

[0112] (5) Calculate the drug release rate: drug release rate (%) = (C3 / C1) × 100%, where C1 is the concentration of the encapsulated drug.

[0113] in accordance with Figure 3 The drug release rate of Examples 1-3 showed a relatively ideal trend. In the initial stage, the drug release was relatively slow. This was because the structure of the coacervate formed by the agglutinated polypeptide was stable and the drug was effectively wrapped therein. As time went by, the drug release gradually increased. This was due to the microenvironmental responsiveness of the coacervate, which could gradually release the drug under specific in vivo environmental conditions. The network structure wrapped on the surface of the coacervate by multiple cross-linked interactions formed by highly substituted sodium hydroxymethyl cellulose, sodium alginate and gallic acid not only improved the stability of the coacervate, but also regulated the drug release rate to a certain extent, so that the drug could be released in an expected manner, thereby achieving targeted controlled release of the drug.

[0114] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0115] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An agglutination polypeptide, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of polylysine polypeptide, 15-25 parts of polyglutamic acid polypeptide, 10-18 parts of arginine oligopeptide, 8-15 parts of high-substituted sodium hydroxymethylcellulose, 5-12 parts of sodium alginate and 3-8 parts of gallic acid; The highly substituted sodium hydroxymethyl cellulose is prepared by the following steps: S1: adding potassium hydroxide to water to prepare a potassium hydroxide solution with a mass fraction of 12-15%, adding sodium sulfite to the potassium hydroxide solution and stirring evenly, then adding copper sulfate, adjusting the temperature to 65-70° C., keeping the temperature and stirring for 40 minutes, to obtain a mixed solution; S2: adding pine pollen to the mixed solution obtained in step S1, stirring at a speed of 1200 r / min for 4-5 hours, standing for 1.5 hours, performing reduced pressure distillation and drying to constant weight to obtain an intermediate; S3: Mix the intermediate obtained in step S2 with the mixed solution, adjust the temperature to 45° C., keep warm and stir for 1.5 hours, then add etherifying agent potassium bromoacetate to carry out etherification treatment for 2.5 hours, neutralize with citric acid to neutrality after the reaction, repeatedly wash with 75% isopropanol solution, and finally perform reduced pressure distillation and dry to constant weight to obtain the highly substituted sodium hydroxymethyl cellulose.

2. The agglutination polypeptide according to claim 1, characterized in that: The mesh number of the pine pollen is 80-120 meshes.

3. The agglutination polypeptide according to claim 2, characterized in that: In step S1, the mass fraction of sodium sulfite is 3.5-4.5%, and the mass fraction of copper sulfate is 0.2-0.25%.

4. The agglutination polypeptide according to claim 3, characterized in that: The mass ratio of the pine wood powder to the new mixed liquid in step S2 is 1:8-10.

5. The agglutination polypeptide according to claim 4, characterized in that: In step S3, the mass ratio of the intermediate to the mixed liquid is 1:13-20.

6. The agglutination polypeptide according to claim 5, characterized in that: In step S3, the mass ratio of potassium bromoacetate to the intermediate is 2.5-5:

1.

7. The agglutination polypeptide according to claim 6, characterized in that: The average molecular weight of the poly-lysine polypeptide is 700,000-1.5 million.

8. The agglutination polypeptide according to claim 7, characterized in that: The average molecular weight of the polyglutamic acid polypeptide is 150,000-3,000,000.

9. The agglutination polypeptide according to claim 8, characterized in that: The number of oligopeptides on the arginine oligopeptide is greater than 5.

10. Use of the agglutination polypeptide according to any one of claims 1 to 9 in a drug delivery system, characterized in that: The pH targeted controlled release range of the agglutination polypeptide is 7.0-8.0.